A Global Oxidation Scheme for Propane-Air Combustion Suitable for Use Into Complex Reacting Flow Computations - KOUTMOS, P.; GIANNAKIS, G.; MARAZIOTI, P. (Engineering Transactions, 2007)
In Direct or Semi-Direct Numerical Simulations of turbulent reacting flows the exploitation of complex, realistic and detailed chemistry and transport models often results in prohibitive memory and CPU requirements when flows of practical relevance are treated. The integrated Combustion Chemistry approach has recently been put forward as a methodology suitable for the integration of complex chemical kinetic and chemistry effects into large scale computational procedures for the calculation of complex and practical reacting flow configurations. Through this procedure, a reduced chemical kinetic scheme involving only a limited number of species and reactions is derived from a detailed chemical mechanism, so as to include major species and pollutants of interest in the main flow calculation. The chemical parameters employed in this integrated scheme i.e. rates, constants, exponents are then calibrated on the basis of a number of constraints and by comparing computations over a range of carefully selected laminar flames so as to match a number of prespecified flame properties such as adiabatic temperatures, selected target species profiles, flame speeds, extinction characteristics. The present work describes such an effort for a commonly used fuel of both the fundamental and practical importance that often is used to simulate the performance of higher hydrocarbons in practical engine simulations, i.e. propane. The proposed nine-step scheme involves nine major stable species and in addition to the basic propane oxidation model also includes NOX production and soot formation submodels.